Which Arterial Cannulation is Better for Acute Type A Aortic Dissection Repair? - L. V. Kulyk; D. M. Beszlej; V. G. Averchuk; I. S. Protsyk; Y. G. Orel; V. P. Fedorenko; A. M. Sterniuk; V. T. Pavlov (Ukrainian Journal of Cardiovascular Surgery, 2016)
It is strongly believed that surgical results of management of acute type A dissection of the ascending aorta (AAD) are influenced by perfusion technique and cannulation site for cardiopulmonary bypass. From January 2010 to March 2016, 120 patients underwent emergency surgical repair of the AAD (mean age 52±25 years, 78 male, 42 female). Medical records of 120 patients who received femoral (70), aortic arch (21), direct ascending aorta (18), carotid (10) or innominate artery (1) cannulation were reviewed. The hospital mortality rate was 12,5% (15 of 120); and not related to cannulation sites. The optimal site for aortic input for the repair of AAD should be chosen according to patient’s status.